2014
DOI: 10.1371/journal.pone.0087502
|View full text |Cite
|
Sign up to set email alerts
|

AtWuschel Promotes Formation of the Embryogenic Callus in Gossypium hirsutum

Abstract: Upland cotton (Gossypium hirsutum) is one of the most recalcitrant species for in vitro plant regeneration through somatic embryogenesis. Callus from only a few cultivars can produce embryogenic callus (EC), but the mechanism is not well elucidated. Here we screened a cultivar, CRI24, with high efficiency of EC produce. The expression of genes relevant to EC production was analyzed between the materials easy to or difficult to produce EC. Quantitative PCR showed that CRI24, which had a 100% EC differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…Su et al (2009) showed the correct WUS expression, controlled by an appropriate exogenous auxin level, to be crucial for the Arabidopsis somatic embryo formation. AtWUS was demonstrated to enhance the conversion of non-embryogenic cells to embryogenic ones during SE in Gossypium hirsutum (Zheng et al 2014). All the results discussed above may indicate that WUS expression takes place early during SE, the expression profile being dependent on the composition of hormones and their concentration in the medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al (2009) showed the correct WUS expression, controlled by an appropriate exogenous auxin level, to be crucial for the Arabidopsis somatic embryo formation. AtWUS was demonstrated to enhance the conversion of non-embryogenic cells to embryogenic ones during SE in Gossypium hirsutum (Zheng et al 2014). All the results discussed above may indicate that WUS expression takes place early during SE, the expression profile being dependent on the composition of hormones and their concentration in the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of AtWUS in Coffea canephora induces callus formation and causes an increase in somatic embryos production (Arroyo-Herrera et al 2008). An identical ectopic expression in Gossypium hirsutum WUS promotes the vegetative-to-embryogenic transition (Zheng et al 2014). Chen et al (2009) investigated WUS and additionally WOX5 and found WUS expression to be essential for M. truncatula callus growth and somatic embryo induction.…”
Section: Introductionmentioning
confidence: 99%
“…An SE-promoting capacity was also indicated for WUSCHEL (WUS), which is a member of the WOX superfamily of the genes encoding the plant-specific homeobox TFs that are involved in promoting cell division and/or preventing the premature cell differentiation of the stem cells in SAM (reviewed in [155,156]). The positive impact of WUS on the embryogenic potential of tissue was indicated given that the gain-of-function mutation in WUS led to the spontaneous formation of somatic embryos on Arabidopsis root explants [157] and an overexpression of WUS promoted or enhanced the embryogenic response in other plants [158][159][160]. Auxin treatment was found to be essential for correctly regulating the WUS expression and the WUS transcripts that were detected in a group of embryogenic callus cells were postulated to indicate an auxin accumulation in the SAM and the pro-embryo [103].…”
Section: Complex Interactions Between the Tf Genes That Control Auxinmentioning
confidence: 99%
“…Few studies involving a genetic transformation in annatto have been performed, including direct and indirect somatic embryogenesis-based transformation system (Parimalan et al 2011) and transient transformation from hypocotyls (Zald铆var- Cruz et al 2003), all mediated by Agrobacterium tumefaciens. On top of that, there is a growing body of literature that reports the usefulness of the embryogenic pathway in genetic transformation protocols Bull et al 2009;Yang et al 2014;. Somatic embryogenesis is a unique system that has also become an appropriate method for studying the morphophysiological and molecular aspects of cell differentiation.…”
Section: Somatic Embryogenesis As a Key Morphogenic Pathway For Genetmentioning
confidence: 99%